COVID-19 in South Asia : An Unequal Shock, An Uncertain Recovery - Findings on Labor Market Impacts from Round 1 of the SAR COVID Phone Monitoring Surveys - World Bank (Washington, DC, 2022)
All countries across South Asia, faced with the rising risks of COVID-19 infection rates, implemented severe economic lockdowns in early 2020 with varying frequencies and time periods. While the exact nature and duration of these lockdowns varied across countries in the South Asia Region (SAR), almost all SAR countries imposed their first economic lockdown in late March 2020 in response to the growing health threat of COVID-19 infections. In India, for instance, the national lockdown was first introduced in late March 2020, which coincided with the imposition of similar lockdowns in Bangladesh, Nepal, and Sri Lanka, followed by a national lockdown in Pakistan on April 1, 2020. By April 17, 2020, the population of all SAR countries was under severe lockdown with varying rules and conditions based on national or local directives. The introduction of these lockdowns led to a drastic, abrupt disruption in all forms of physical mobility and economic activities. Trends from the Google COVID-19 Community Mobility data reveal this sharp drop in day-to-day mobility related to four different types of economic activity across 6 out of 8 SAR countries for which this data was available. Figure 1 plots the daily change in the Google Mobility index, which is constructed by taking an equally weighted mean across the four dimensions of economic activity for the five weeks before March 2020. In the six SAR countries, the average mobility remained approximately, on average, 58 percent below their respective pre-COVID levels during the first week of the lockdown. For example, in Nepal, where the lockdown was first introduced on March 24, 2020, mobility (as measured by the Google Mobility index) was 66 percent below pre-COVID levels on the first day of the lockdown; and it remained, on average, 71.5 percent below per-COVID levels between March 24, 2020, and March 30, 2020. We observe a similar pattern of immediate and large disruptions in mobility in all SAR countries, except in Afghanistan (22.5 percent below pre-COVID levels), where restrictions were more localized. The Google Mobility index closely follows these changes in rules and conditions in SAR countries, which varied over time within each country as well as across countries. In countries like Nepal, India, and Sri Lanka, with an extended period of restrictions imposed through national or local directives at different points in time, mobility had not returned to pre-COVID levels even as late as April 2021. In Nepal and Sri Lanka, where the second lockdown was introduced in August and November 2020, respectively, we observe a sharp drop again in mobility after a gradual recovery following the easing of the first lockdown. In other SAR countries like Afghanistan, Bangladesh, and Pakistan, mobility only returned to pre-COVID levels between September and October 2020. These results underscore the dramatic and prolonged impact that COVID-19 induced lockdowns have had on mobility and economic activity, which is perhaps unprecedented in the region, at least in recent history4. These lockdowns are likely to have important implications on various socio-economic dimensions of welfare, including labor market outcomes, both immediately and in the medium, to long-term. More importantly, the long-term impacts will also be determined by the nature and the pace of recovery observed in these countries in the months and years after the initial phase of lockdown. Moreover, the emergence of new mutants leaves open the possibility of future lockdowns as a policy response to mitigate the health effects of the virus, which could impact economic activity and reverse observed recoveries.